Self-management of diabetes - S. V Nedogoda (КардиоСоматика, 2013)
The theory based on the supposition that for the effective treatment of diabetes patients should largely take responsibility for their health, is of no doubt. This is only possible if patients are properly trained to perform continuous monitoring of their disease and have at their disposal some modern easily manageable blood glucose meters that meet international standards and. The present article highlights the changes in the last revision of national guidelines related to the treatment of self-control, as well as existing modern demands in instrumentation for glycemic control.